The Administration Strategy for the Vocational Sector of Non-formal Private Schools, Chiang Mai Province - Saejeng, Panomporn; Muenjaem, Samnao; Puthaprasert, Choocheep; Poungkaew, Phubet (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2025)
The objectives of this multi-phase mixed methods research were 1) to synthesize components of the administrative for the vocational sector of non-formal private schools, Chiang Mai Province; 2) to study the needs assessment of the administration for the vocational sector of non-formal private schools, Chiang Mai Province; and 3) to develop the administrative strategies for the vocational sector of non-formal private schools, Chiang Mai Province. Key informants consisted of 133 respondents, the instruments used were a synthesis table, a confirmation form, and a questionnaire. The data were analyzed by frequency, percentage, mean, standard deviation, and PNI Modified. The study results revealed as follows: 1. The components of the administration after confirmation consisted of six core components as follows: general administration, academic administration, budget administration, personnel administration, network management, and technological administration; 2. The priority needs of the administration for the vocational sector of non-formal private schools, Chiang Mai Province were technological administration (0.09), followed by budget administration (0.07), general administration (0.06), and academic administration (0.05), respectively. 3. The components of the administration strategies for the vocational sector of non-formal private schools under Chiang Mai Province consisted of one vision, four missions, one goal, and five strategies with twenty-six measures.